Uma Abordagem reflexiva sobre o Ensino da Análise Combinatória na Educação Básica - Pereira, Gedilson Pacheco (2019)
The great difficulty presented by the protagonists of the current educational system, that is, teachers and students, regarding the teaching and learning of Combinatorial Analysis, was what motivated us to carry out this study; which has, among other objectives, a pedagogical reflection on the teaching and learning of Combinatorial Analysis. We have prepared some proposals that we consider essential for the good development of this content in basic education. Taking into account the great importance that Combinatorial Analysis has for the student's logical and cognitive reasoning, in this work we present a little of its history, further strengthening its great importance for the present day. We took a reflective approach to how the content of Combinatorial Analysis has been approached in elementary and high school, in which we defend in this work the non-use of merely mathematical formulas that in most cases are adopted mechanically, without any connection with the reality of the world. student, without valuing the ability to create and produce. We present some activities, and from them we realize the importance of working in groups, the multiple interactions, the different perceptions that students have when solving a problem, the conflicts that arise, the high level of concentration established by the proposed activity, the importance of play in education, the theory of error. The work also reflects on the approach to content taken by textbooks, its contextualization, and how Analysis content is worked on in undergraduate mathematics courses.